Interday reliability of a testing battery to assess lateral symmetry and performance in well-trained volleyball players - Iglesias-Caamaño, M.; Álvarez-Yates, T.; Carballo-López, J.; Cuba-Dorado, A.; García-García, O. (The Journal of Strength and Conditioning Research, 2022)
This study aimed to determine the relative and absolute interday reliability of a testing battery for lateral asymmetry detection and performance in well-trained volleyball players and to determine whether retaining for analysis the best or the average value of 3 attempts would modulate the interday reliability and the magnitude of asymmetry. Thirteen Superleague-2 male volleyball players performed on 3 different days a 5-test battery composed of 4 tests for assessing muscle asymmetries: active knee extension, Y-balance test (YBT), modified 20-yard shuttle run (M-20Y), and single-leg countermovement jump; and one for volleyball sports performance: attack jump (AJ). The intraclass correlation index and coefficient of variation (CV) together with the standard error of measurement (SEM, %SEM) and the minimum detectable change (MDC, %MDC) were taken to calculate relative and absolute reliability. Two-way repeated-measures analysis of variance was used to establish the differences between the best value and the average value in each session. The low %MDC (<10%) suggests that all the tests that make up the testing battery would have good sensitivity to detect possible asymmetries. All tests have shown an excellent interday absolute reliability (CV <4.5%; %SEM < 5%), both when retaining the best value and the average value of the 3 attempts. In addition, AJ and YBT (on both legs) obtained a good-excellent relative reliability, whereas the M-20Y test seems to show a lower relative reliability. Retaining the best value or the average value to determine the magnitude and direction of asymmetry seems to be equally reliable with no differences between both values.